The editor of Gazeta Toruńska Hieronim Derdowski in the Toruń court - Gzella, Grażyna (Folia Toruniensia, 2011)
The work of Hieronim Derdowski in the editorial office of Gazeta Torunska as an editor did not only consist in preparing materials for print in the periodical. Being responsible for editing, he also bore consequences for publishing individual articles, notes and correspondence, which very often led to searches in his house and the printing shop, interrogations, accusations and press trials. Derdowski, responsible for the paper, worked in the editorial office from 1879 to 1884 with breaks, and in this period of time he was brought to court seven times. The first three trials finished with freeing him, but the next ones resulted in Derdowski's being convicted. In the subsequent four trials Derdowski was given a fine of 500 marks in total or 55 days in prison. It must have been a large amount of money as the poor editor went to prison to cover part of the fine.